Community Economic Empowerment (Case Study on the Community of Cracker Makers Jengkol) in Korong Jambak, Padang Pariaman - Reval, Diken; Sunarti, Vevi (Universitas Negeri Padang, 2024)
This research is that there are a large number of natural resources in Indonesia and various types and forms, one of which is jengkol, especially in the Nagari Kasang area, Padang Pariaman Regency which can improve human resources in terms of work. It is very clear that the process of processing jengkol into jengkol crackers in Korong Jambak Nagari Kasang is very helpful for the economy there, not only processing it into jengkol crackers, all the work is done by the people in Korong Jambak Nagari Kasang. This study aims (1) to determine community involvement in related elements in coaching. (2) knowing the implementation of learning between craftsmen, (3) knowing environmental support for jengkol cracker business, (4) knowing jengkol cracker marketing techniques.This study uses a qualitative approach with the type of case study which is expected to provide an overview of the research results. The setting of this research was conducted in Korong Jambak, Nagari Kasang, Padang Pariaman Regency. The source of this research was obtained from the jengkol cracker-making community. Data collection techniques used in this study were interviews, observation and documentation. The validity of the data obtained from this study is by theoretical triangulation.The results of the study show that: (1) There is involvement of related elements in the form of support in the form of promotions and material assistance in coaching activities for the community (2) There are learning activities among fellow craftsmen in the form of cooperation and giving advice to each other, (3) There is support the environment for the jengkol cracker business physically and non-physically which is the economic empowerment of the people in Korong Jambak (4) The existence of marketing techniques for the jengkol cracker business by marketing Offline and Online (5) Results and impacts felt by jengkol cracker makers with empowered communities for the family and also the economic changes felt by the community itself.